2021
DOI: 10.3390/s21020483
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Compatible Lead-Free Piezoelectric Composite for Acoustophoresis Based Particle Manipulation Techniques

Abstract: This research paper is concentrated on the design of biologically compatible lead-free piezoelectric composites which may eventually replace traditional lead zirconium titanate (PZT) in micromechanical fluidics, the predominantly used ferroelectric material today. Thus, a lead-free barium–calcium zirconate titanate (BCZT) composite was synthesized, its crystalline structure and size, surface morphology, chemical, and piezoelectric properties were analyzed, together with the investigations done in variation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…In addition, the grain size was carried out on TEM image and (D TEM ) is ~ less than 50 nm ( Figure 7 b). For scaffold, the D TEM value is almost larger than the extracted crystallite size from Monshi–Scherrer equation, which can be explained by the fact that a grain consists of more than one crystallite and it is related to the nucleation and growth of the particles [ 48 , 49 , 50 , 51 ]. …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the grain size was carried out on TEM image and (D TEM ) is ~ less than 50 nm ( Figure 7 b). For scaffold, the D TEM value is almost larger than the extracted crystallite size from Monshi–Scherrer equation, which can be explained by the fact that a grain consists of more than one crystallite and it is related to the nucleation and growth of the particles [ 48 , 49 , 50 , 51 ]. …”
Section: Resultsmentioning
confidence: 99%
“…The manipulation of microparticles is very important for many disciplines and sectors, such as micromachine technology, biotechnology, cell biology, material processing, semiconductor industries, and neuroscience [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Handling, transportation, and manipulation of microparticles or bulk and granular materials can be implemented by various methods and approaches that can generally be divided into two types: prehensile and non-prehensile.…”
Section: Introductionmentioning
confidence: 99%
“…Parts on a horizontal platform can be moved by various means. For example, this can be performed by using parallel manipulators [ 1 , 2 , 3 , 4 ] by applying piezoelectric or electromagnetic actuated planar micromanipulators [ 5 , 6 , 7 , 8 ], by pushing with robot end-effectors [ 9 , 10 , 11 ], by transporting with devices which move together with the parts to be displaced (e.g., mobile robots) [ 12 , 13 , 14 ], by employing actuator arrays under a flexible surface [ 15 ], by applying acoustic manipulation techniques [ 16 , 17 , 18 , 19 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the part can be moved along a defined trajectory by controlling the frequencies and the phase shift. A vibrating trough with finlike asperities was employed for handling of granular materials by Chen et al [ 18 ]. The directional movement of the material was caused by the force asymmetry generated by the finlike asperities.…”
Section: Introductionmentioning
confidence: 99%